Coal-based carbon / carboxymethyl cellulose photo-thermal sponge as well as preparation method and application thereof
By using coal-based carbon/carboxymethylcellulose photothermal sponge material (CMC@MC) as the core material of solar interface evaporators, the problems of equipment stability and energy consumption in high mineralization mine water treatment are solved, and efficient and low-cost water evaporation effect is achieved.
Patent Information
- Application Number
- CN202411674409.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
In the prior art, when dealing with high mineralization mine water, the equipment is difficult to operate stably for a long time, and there are problems such as high energy consumption, high cost and easy corrosion of the equipment.
Coal-based carbon/carboxymethylcellulose photothermal sponge material (CMC@MC) is used as the core material of the solar interface evaporator. Through the photothermal conversion of coal-based carbon material and the porous structure of carboxymethylcellulose sponge, efficient water evaporation is achieved.
The evaporation rate of high-mineralization mine water has been significantly improved, with low energy consumption and low cost, and good salt resistance of the material. The evaporation rate has not been significantly reduced after recycling, and the salt content has been significantly reduced.
Smart Images

Figure CN119684684A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-mineralization mine water recovery and treatment, and relates to a high-efficiency carbonaceous photothermal conversion material and a preparation method thereof, and application of the material in interfacial evaporation treatment of high-mineralization mine water. Background Art
[0002] Mine water is formed when underground water or surface water near the excavation tunnel or coal seam penetrates or flows into the tunnel through water-conducting cracks during the coal mining process. High-mineralized mine water generally refers to mine water with a total dissolved solid (TDS) greater than 1000 mg / L. Its salts mainly come from substances such as sulfates and carbonates in the coal seams, and the water quality is mostly neutral or alkaline. According to statistics, about 30% of mine water in my country is high-mineralized mine water, and the proportion of high-mineralized mine water in the northwest region exceeds 50%. There are great differences in the water quality characteristics of mine water in different regions. The geological conditions, characteristics of coal seams, methods of coal mining, and the surrounding environment will affect the composition and content of mine water. The mine water in coal mines in the Yellow River Basin in the northwest is highly alkaline, generally alkaline or weakly alkaline, with a pH between 7 and 9; the coal-bearing strata in the northern region contain a small amount of fluoride minerals, and the mine water in the area where they are located contains a higher concentration of fluoride; some coal mines in Shaanxi Province and Inner Mongolia Autonomous Region have Na + and Ca 2+ The concentration is relatively high, the SO4 2- and HCO3 - The concentration is relatively high; the Shenhua mining area contains high-fluoride mine water and all of it is sodium type.
[0003] Due to the large amount of water evaporation in arid areas, the concentration of groundwater salt will lead to further increase in salinity. In many arid and semi-arid areas in the west, the ecological environment is fragile, water resources are scarce, and there is a lack of receiving water bodies. The continuous increase in coal production has led to a corresponding increase in mine water. If high-mineralization mine water is directly discharged, it will cause soil salinization, ecological environment damage, water resource waste and other problems. Therefore, the effective treatment and resource reuse of high-mineralization mine water is a severe challenge facing the coal industry. Some local environmental protection departments have required that mine water cannot be discharged. The current typical process flow for treating high-mineralization mine water is divided into pretreatment, membrane concentration treatment and concentrated brine evaporation and crystallization. Membrane concentration and reduction processes include reverse osmosis, electrodialysis and other technologies. However, membrane concentration systems are usually difficult to operate stably for a long time due to the long treatment process and high energy consumption per ton of water. Common evaporation and crystallization technologies include mechanical vapor recompression evaporation and multi-effect evaporation. These two technologies still have problems such as high cost, high energy consumption and easy corrosion of equipment.
[0004] Photothermal desalination technology uses photothermal conversion materials to convert light energy into heat energy to evaporate high-concentration salt water. This technology has low energy consumption, a wide range of applications, and good application prospects. Interface evaporation is achieved by floating photothermal materials on the water surface. The heat generated by photothermal conversion is concentrated at the interface to achieve a similar focusing effect. The evaporation rate and energy utilization efficiency are greatly improved, significantly improving the problems of slow traditional evaporation rate and low energy utilization efficiency.
[0005] Chinese patent application 202211626810.9 discloses a method for preparing a photothermal coating composite material for solar interface evaporation, wherein pyrrole is dissolved in ethanol to obtain a pyrrole solution; tannic acid is dissolved in a Tris-HCl buffer solution to obtain a tannic acid solution; the obtained pyrrole solution and tannic acid solution are evenly mixed to obtain a tannic acid-pyrrole mixed solution. The porous substrate is immersed in the prepared tannic acid-pyrrole mixed solution, then taken out and immersed in the prepared ferric chloride solution, washed and dried to obtain the tannic acid-polypyrrole photothermal coating composite material. The material has excellent photothermal response performance and the characteristics of rapid water diffusion, but the evaporation efficiency is not high.
[0006] Chinese patent application 202311721523.0 discloses a polypyrrole / diatomite-porous foam composite photothermal material and its preparation method and application. The photothermal agent polypyrrole is obtained by oxidative polymerization of pyrrole monomer and oxidant under acidic conditions. The pyrrole monomer is dissolved in deionized water, and a certain amount of diatomite and dilute hydrochloric acid are added to prepare a pyrrole / diatomite dispersion; the obtained pyrrole / diatomite dispersion is coated on the polymer porous foam, and in-situ oxidative polymerization is carried out, and it is placed in a blast drying oven to dry, and a polypyrrole / diatomite-porous foam composite photothermal material is obtained. The prepared composite photothermal material has a stable structure and excellent photothermal conversion performance and salt resistance. It is also a photothermal conversion material with a prospect of large-scale standardized preparation, and can be used in occasions such as high-salinity seawater desalination.
[0007] Chinese patent application 202310575769.5 discloses a method for preparing a photothermal sponge for solar-driven evaporation and auxiliary wastewater purification, wherein the bamboo is cut into segments and subjected to a series of processes to obtain flocculent delignified bamboo fiber; the biochar is then mixed with N,N-dimethylformamide, zirconium chloride and 2-aminoterephthalic acid, heated in a reactor, centrifuged, washed and dried to obtain C@MOF powder; the delignified bamboo fiber and chitosan are added to an acetic acid aqueous solution and stirred, and then C@MOF powder is added to obtain a black non-Newtonian flow, which is transferred to a silica gel mold for unidirectional freezing to form a polymer network structure of the photothermal sponge, then freeze-dried, immersed in a NaOH solution for cross-linking treatment, and the photothermal sponge CS / BFs / C@MOF is obtained. The material has good water transport and self-cleaning properties, but the study only simulates the purification effect of polluted water bodies, and does not reflect effective performance for water with high salt content such as high-mineralization mine water. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention is based on solar interfacial evaporation technology and aims to provide a coal-based carbon / carboxymethyl cellulose photothermal sponge material CMC@MC and its application in the efficient removal of highly mineralized mine water.
[0009] In a first aspect, the present invention provides a coal-based carbon / carboxymethyl cellulose photothermal sponge material (CMC@MC), in which a coal-based carbon material MC having a photothermal conversion function is uniformly distributed inside the carboxymethyl cellulose sponge CMC to form a porous structure material.
[0010] Preferably, a plurality of porous structural materials are disposed on the foam substrate.
[0011] Specifically, the foam substrate refers to a polystyrene foam board.
[0012] In a second aspect, the present invention provides a method for preparing the coal-based carbon / carboxymethyl cellulose photothermal sponge material according to the first aspect, comprising the following steps:
[0013] (3) The coal sludge is dried, crushed, calcined under nitrogen, pickled, dried, and ground to obtain a coal-based carbon material;
[0014] (4) Sodium carboxymethyl cellulose, α-cellulose, polyacrylic acid, and coal-based carbon material are added to water in a mass ratio of 10:10:1 to 6:4, and stirred evenly. The resulting precursor solution is frozen into a solid state, and then vacuum freeze-dried, and finally vacuum cross-linked at 100° C. for 20 to 30 hours to obtain CMC@MC.
[0015] Preferably, in step (1), calcination is carried out at 800° C. for 2 h under nitrogen.
[0016] Preferably, in step (2), the mixture is freeze-dried in vacuum at -45°C to -35°C for 30 to 40 hours.
[0017] In a third aspect, the present invention provides an application of the coal-based carbon / carboxymethyl cellulose photothermal sponge material described in the first aspect in the treatment of highly mineralized mine water by solar interfacial evaporation.
[0018] Furthermore, the salt contained in the high-mineralization mine water is sodium chloride, and the salt content is 3.5-20wt%.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The coal-based carbon material of the present invention is derived from coal slime, a byproduct of coal processing. The present invention utilizes coal slime as a resource, has a simple preparation process, and is low in cost. Adding it to the sponge effectively improves the light absorption and photothermal conversion performance of the material. It has a simpler carbonization process and greater application potential among similar biomass-based carbon materials.
[0021] (2) The carboxymethyl cellulose sponge of the present invention has a controllable 3D porous structure and is highly hydrophilic, which is conducive to the scattering of light inside its pores and improves the light absorption and photothermal conversion capabilities of coal-based carbon materials. The sponge-like polymer is synthesized by the esterification reaction of polyacrylic acid and sodium carboxymethyl cellulose at high temperature. The pore size of the sponge can be controlled by changing the dosage of polyacrylic acid. At the same time, the carboxymethyl cellulose sponge is also highly portable and flexible, and can adapt to various complex application conditions.
[0022] (3) The core of the 3D solar interface evaporator of the present invention is a coal-based carbon / carboxymethyl cellulose photothermal sponge. The sponge has a strong upward capillary water transport capacity and can continuously transfer the bottom aqueous solution to the top. The evaporation site is much higher than that of the traditional membrane interface evaporation device. The coal-based carbon / carboxymethyl cellulose photothermal sponge has good thermal insulation ability and good salt resistance. After recycling, the evaporation rate does not decrease significantly. The salt ion concentration of the condensed water after evaporation is significantly reduced.
[0023] (4) Combined with the above technical advantages, the evaporation rate of high-mineralized mine water by sponge is greatly improved. For example, under one solar equivalent, the evaporation rate of CMC@MC photothermal evaporation device reaches a maximum of 3.72 kg·m -2 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the solar-driven interfacial evaporator device with coal-based carbon / carboxymethyl cellulose photothermal sponge as the core.
[0025] Figure 2 This is a flow chart for preparing the coal-based carbon / carboxymethyl cellulose photothermal sponge of the present invention.
[0026] Figure 3 The coal-based carbon material (a) of the present invention, and CMC 10 / 4 Scanning electron micrographs of @MC at low (b) and high (c) magnifications.
[0027] Figure 4 To test CMC 10 / 4 @MC and other control samples’ light absorption, photothermal conversion and evaporation performance; (a) is CMC 10 / 4 @MC and CMC 10 / 4 UV-visible-near infrared absorption spectrum of (b) CMC 10 / 4 @MC, CMC 10 / 4 and the surface temperature variation of MC@cellulose membrane within 30 min; (c) 1 kW·m -2 CMC under light 10 / 4 @MC is a graph showing the change in liquid mass as a result of evaporating a 20 wt% NaCl solution and monitored and recorded in real time by a computer; (d) is a graph showing the evaporation rate based on the change in liquid mass.
[0028] Figure 5 To test CMC 10 / 4 @MC salt tolerance effect diagram, where (a) is CMC 10 / 4 @MC is a graph of the liquid mass change during the evaporation of NaCl solutions of different concentrations monitored and recorded by a computer in real time; (b) is a graph of the evaporation rate obtained based on the change in liquid mass; (c) is 1kW·m -2 CMC under light 10 / 4 @MC is the evaporation rate diagram of 10 cycles of use in 20wt% NaCl solution; (d) is CMC 10 / 4 @MC Evaporation rate graph for 3 consecutive days, eight hours per day. DETAILED DESCRIPTION
[0029] In order to further understand the technical solution of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0030] The concept of the present invention is: the present invention pre-prepares a composite material based on solar-driven interfacial evaporation technology, and uses this material as the core to build a solar-driven interfacial evaporator device for evaporating and concentrating high-mineralization mine water. The composite material is a coal-based carbon / carboxymethyl cellulose photothermal sponge, wherein the coal-based carbon is the photothermal material, and the carboxymethyl cellulose sponge is the carrier of the coal-based carbon material. The material is arranged on a foam substrate, floating on the surface of the high-mineralization mine water, and then the whole is placed in a transparent container with a slope at the top. Under the radiation of sunlight, water vapor condenses at the top to form water droplets, which gather downward along the slope of the container and are collected at the bottom, thereby realizing the treatment and recovery of high-mineralization mine water. Figure 1 Schematic diagram of the solar-driven interfacial evaporator device with coal-based carbon / carboxymethyl cellulose photothermal sponge as the core.
[0031] Example 1
[0032] Combination Figure 2 , this embodiment provides the preparation process of the coal-based carbon / carboxymethyl cellulose photothermal sponge.
[0033] The coal slime obtained from a coal mine was placed in a 60°C oven for drying. After the coal slime was completely dried, it was fully crushed with a crusher. A certain amount of crushed coal slime was placed in a tubular furnace and heated at 800°C under N2 atmosphere. The calcined product was acid-washed 3 times with 1mol / L HCl, then washed with ultrapure water until neutral, filtered and dried overnight in a 100°C oven, and then ground to obtain a coal-based carbon material, which was recorded as MC. 2.5g sodium carboxymethyl cellulose, 2.5g α-cellulose, a certain amount of polyacrylic acid, and 1g coal-based carbon material were dispersed in 100mL deionized water and mechanically stirred for 1.5h to obtain a uniformly mixed precursor solution. After aging, the precursor dispersion was poured into a cylindrical mold and then placed in a refrigerator for freezing for 12h. The completely frozen precursor solution was vacuum freeze-dried at -40°C for 36h, and then placed in a vacuum oven at 100°C for cross-linking for 24h, thereby obtaining a coal-based carbon / carboxymethyl cellulose photothermal sponge. In order to find the optimal porosity of carboxymethyl cellulose sponge, so as to give full play to the photothermal conversion performance of coal-based carbon materials, the dosage of polyacrylic acid was adjusted, and sodium carboxymethyl cellulose and polyacrylic acid were prepared in six ratios of 10:1, 10:2, 10:3, 10:4, 10:5, and 10:6, respectively. The six coal-based carbon / carboxymethyl cellulose photothermal sponges were named CMC 10 / 1 @MC, CMC 10 / 2 @MC, CMC 10 / 3 @MC, CMC 10 / 4 @MC, CMC 10 / 5 @MC, CMC 10 / 6 @MC.
[0034] Under the irradiation of one equivalent solar light, the evaporation performance of these six coal-based carbon / carboxymethyl cellulose photothermal sponges for 20wt% NaCl solution was recorded. The test time was two hours. The computer monitored and recorded the mass change of the liquid in real time, and calculated the evaporation rate of the sponge. As shown in Table 1, the evaporation performance of these six coal-based carbon / carboxymethyl cellulose photothermal sponges for 20wt% NaCl solution was recorded in detail.
[0035] Table 1 Evaporation performance of six coal-based carbon / carboxymethyl cellulose photothermal sponges for 20 wt% NaCl solution
[0036]
[0037] As shown in Table 1, the evaporation rate of the coal-based carbon / carboxymethyl cellulose photothermal sponge will change with the change of the amount of polyacrylic acid added. 10 / 4 @MC means that when the ratio of sodium carboxymethyl cellulose to polyacrylic acid is 10:4, the sponge shows the best evaporation rate, so CMC is selected. 10 / 4 @MC to explore further.
[0038] Figure 3 (a) is a SEM image of the coal-based carbon material MC. The coal-based carbon is tightly stacked together in a multi-layer structure, presenting a uniform and compact state. Figure 3 (b) is CMC 10 / 4 @MC surface SEM image, you can see CMC 10 / 4 @MC surface has a porous structure with a large pore size distribution, and the maximum pore diameter can reach 100μm. Figure 3 (c) in the figure is CMC 10 / 4 @MC's morphology under a high-power scanning electron microscope shows that flaky coal-based carbon is evenly distributed on the sponge skeleton, proving that the coal-based carbon is successfully compounded into the carboxymethyl cellulose sponge.
[0039] Example 2
[0040] In order to verify that the addition of coal-based carbon materials to carboxymethyl cellulose sponge can enable the carboxymethyl cellulose sponge to have the ability to convert light energy into heat energy, and that the 3D porous structure of carboxymethyl cellulose sponge is conducive to the photothermal conversion of coal-based carbon materials, the CMC in Example 1 was used to 10 / 4 @MC, CMC 10 / 4 Control experiments were carried out using carboxymethyl cellulose (carboxymethyl cellulose sponge prepared without adding coal-based carbon material when the ratio of sodium carboxymethyl cellulose to polyacrylic acid was 10:4) and MC@cellulose membrane (coal-based carbon material MC was loaded onto the cellulose membrane by vacuum filtration, wherein the cellulose membrane was a polyvinylidene fluoride membrane).
[0041] Test CMC separately 10 / 4 @MC and CMC10 / 4 The light absorption capacity in a wide spectral range (200-2500nm) was characterized using an ultraviolet-visible-near infrared (UV-Vis-NIR) spectrophotometer. Figure 4 As shown in (a). CMC 10 / 4 The light absorption rate of CMC is only 42.15%, but after compounding with coal-based carbon materials, 10 / 4 @MC light absorption rate reaches 96.46%. Photothermal conversion performance is as follows Figure 4 As shown in (b), under 1 sun equivalent irradiation, CMC 10 / 4 @MC surface temperature can reach 68℃, while CMC 10 / 4 It can only reach 46°C. In addition, the temperature of MC@cellulose film can only reach 53°C under 1 sun equivalent. 10 / 4 The 3D porous structure of @MC is conducive to the scattering of light inside its pores, thereby enhancing light absorption and photothermal conversion, demonstrating the significant advantages of 3D solar interface evaporators over 2D evaporators.
[0042] Furthermore, in order to improve the utilization rate of floor space, the changes in the water evaporation rate of coal-based carbon / carboxymethyl cellulose photothermal sponges at different heights were studied. 10 / 4 @MC height, solar evaporation experiment on 20wt% NaCl solution. Figure 4 (c) in the figure is the change in liquid mass monitored and recorded in real time by the computer. Figure 4 (d) is the evaporation rate obtained based on the change in liquid mass. 10 / 4 @MC's effective height increased from 1 cm to 2.5 cm, and the water evaporation rate increased from 3.09 kg·m -2 ·h -1 Increased to 4.08kg·m -2 ·h -1 Increasing the height of the sponge can increase the speed of water evaporation. When the height increases to 3cm, the evaporation rate decreases. The sponge with a height of 2.5cm shows the best evaporation performance, but after evaporation for more than two hours, salt deposition will appear on the surface. In order to achieve long-term and efficient operation, the best height is 2cm.
[0043] Example 3
[0044] Salt tolerance is one of the most important indicators for measuring the application value of solar interface evaporators. -2 Under lighting conditions, CMC 10 / 4 @MC evaporation performance for different NaCl concentrations (3.5wt%, 10wt% and 20wt%). Figure 5(a) in the figure is the change of liquid quality monitored and recorded by computer in real time. Figure 5 (b) is the evaporation rate obtained based on the change in liquid mass. When the NaCl concentration is 3.5wt% (approximately the salinity of seawater), the evaporation rate relative to pure water remains almost unchanged. As the NaCl concentration further increases, the evaporation rate shows a slight decrease, but at 20wt% NaCl (approximately the salinity of high-mineralization mine water reverse osmosis concentrate), the evaporation rate can still reach 3.76kg·m -2 ·h -1 , the material has good stability under high salt conditions. Figure 5 As shown in (c), at 1kW·m -2 Under light, CMC 10 / 4 After 10 cycles of use of @MC in 20wt% NaCl solution, its evaporation rate did not decrease significantly. Figure 5 As shown in (d), under evaporation for 8 hours per day for 3 consecutive days, CMC 10 / 4 @MC can still maintain a high evaporation performance, indicating that the sponge has good cyclic stability, laying a good foundation for subsequent practical applications.
Claims
1. A coal-based carbon / carboxymethyl cellulose photothermal sponge, characterized in that: The coal-based carbon material with photothermal conversion function is evenly distributed inside the carboxymethyl cellulose sponge to form a porous structure material.
2. The coal-based carbon / carboxymethyl cellulose photothermal sponge according to claim 1, characterized in that: A plurality of porous structural materials are disposed on the surface of the foam substrate.
3. The coal-based carbon / carboxymethyl cellulose photothermal sponge according to claim 1, characterized in that: The foam substrate refers to a polystyrene foam board.
4. A method for preparing the coal-based carbon / carboxymethyl cellulose photothermal sponge material according to any one of claims 1 to 3, characterized in that: The steps include: The coal-based carbon material is obtained by drying, crushing, calcining under nitrogen, acid washing, drying and grinding the coal sludge; Sodium carboxymethyl cellulose, α-cellulose, polyacrylic acid and coal-based carbon material are added to water in a mass ratio of 10:10:1~6:4 and stirred evenly. The resulting precursor solution is frozen into a solid state and then vacuum freeze-dried. Finally, it is vacuum cross-linked at 100°C for 20~30 h to obtain a coal-based carbon / carboxymethyl cellulose photothermal sponge.
5. The method according to claim 4, characterized in that In step (1), calcination is performed at 800°C for 2 h under nitrogen.
6. The method according to claim 4, characterized in that In step (2), the mixture is freeze-dried under vacuum at -45°C to -35°C for 30 to 40 hours.
7. Use of the coal-based carbon / carboxymethyl cellulose photothermal sponge material as described in any one of claims 1 to 3 in the treatment of highly mineralized mine water by solar interfacial evaporation.
8. The use according to claim 7, characterized in that The salt contained in highly mineralized mine water is sodium chloride, with a salt content of 3.5~20wt%.
Citation Information
Patent Citations
Preparation method of photo-thermal coating composite material for solar interface evaporation
CN115975499A
Photo-thermal sponge for solar-driven evaporation and auxiliary wastewater purification and preparation method of photo-thermal sponge
CN116589745A
Polypyrrole / diatomite-porous foam composite photo-thermal material as well as preparation method and application thereof
CN117924796A
Preparation method of composite carbon material flexible supercapacitor electrode
CN110233065A
Carbon fiber photo-thermal conversion material and application in purifying and recovering of multi-medium solvent
CN111249757A